Sublethal Toxic Effects of Gusathion-A on the Morphology of the Hepatocytes of Cyprinus carpio - Dorado, Emma; Herrera, Annabelle (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
Cyprinus carpio fingerlings were exposed to sublethal levels if 0.05 ppm and 0.1 ppm Gusathion-A for 30 days. Cell disarray, hepatocyte necrosis and vacuolation were observed. Ultrastructural change in the hepatocytes was loss if structural integrity of the plasma membrane, nuclear membrane, endoplasmic reticulum and mitochondria and other cell structures. Glycogen deposits were depleted.